EXTRACTION AND CHARACTERIZATION NATURAL CLAY OF CENTRAL KALIMANTAN AS ONE OF ALTERNATIVES ADDITIVES OF GEOPOLIMER CONCRETE - Karelius (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
Extraction and characterization of natural clay from Central Kalimantan in form of white clay, yellow clay and red clay as one of the alternative additives of geopolymer concrete has been done. The natural clay from Central Kalimantan was first cleaned and then extracted to remove impurities minerals. The extraction was done chemically with 3M HCl solution and continued with calcination at 500 Â° C. Characterization of natural clays, clays extracted by FTIR spectroscopy (Fourier Transform Infrared), XRD (X-ray diffraction), N2 isothermal isothermal fisisorption using gas sorption analyzer based on BET equation. The results of analysis using FTIR and XRD gas sorption analyzer and showed that the main content of natural clay minerals from Central Kalimantan is monmorilonite, halloysite, chrysotile, gibbsite, quartz, anatase, oligoclase, illit, biotite. The results showed that the extraction performed was able to increase the specific surface area of clay, the relative composition of the monmorillonite and quartz minerals, and in turn decreased the relative abundance of the biotite, chrysotile, gibbsite, oligoclase, anatase and illitant minerals which are clay minerals from Central Kalimantan , so that with high content of momorilonite and quartz and large surface area, natural clay as extraction results from Central Kalimantan can be used as an alternative additives of geopolymer concrete.